Public administration in Europe - Pommer, Evert; van Houwelingen, Pepijn (Journal of Public Governance, 2016)
Why do some public administrations perform better than others? This is an important question because the performance of public administration is an important factor of a country’s competitiveness and economic outcomes. Our outcome index for public administration captures ‘good governance’, which includes the six components of the World Bank index, representing responsiveness, effectiveness, and legitimacy of governments. Northern Europe scores especially well on good governance, followed by Oceania, Western Europe, Northern America, and Eastern Asia. Central, Eastern, and Southern Europe obtained the lowest scores in the public administration outcome index. Professionalism (as a dimension of the quality of public administration), freedom of the press, the degree of decentralization, and intensity of ICT expenditure were significantly positively correlated with good governance. Spending on tax administration, on the other hand, was significantly negatively correlated with good governance.